Ain Shams University- Paving the way towards a paperless University - Sherien Elagroudy; Wesam M Elbardisy; Ghada F Hassan; Abdelfattah Saoud; Mahmoud A.S. El-Meteini (Universitas Diponegoro, 2023)
The conventional use of paper-based operations in daily working practices introduces numerous risks and financial burdens. Nowadays, Universities are aligning with the growing movement of